Increased Heme Oxygenase 1 Expression upon a Primary Exposure to the Respiratory Syncytial Virus and a Secondary Mycobacterium bovis Infection - Gisela Canedo-Marroquín; Jorge A. Soto; Catalina A. Andrade; Susan M. Bueno; Alexis M. Kalergis (MDPI AG, 2022)
The human respiratory syncytial virus (hRSV) is the leading cause of severe lower respiratory tract infections in infants. Because recurrent epidemics based on reinfection occur in children and adults, hRSV has gained interest as a potential primary pathogen favoring secondary opportunistic infections. Several infection models have shown different mechanisms by which hRSV promotes immunopathology to prevent the development of adaptive protective immunity. However, little is known about the long-lasting effects of viral infection on pulmonary immune surveillance mechanisms. As a first approach, here we evaluated whether a primary infection by hRSV, once resolved, dampens the host immune response to a secondary infection with an attenuated strain of Mycobacterium bovis (M. Bovis) strain referred as to Bacillus Calmette-Guerin (BCG). We analyzed leukocyte dynamics and immunomodulatory molecules in the lungs after eleven- and twenty-one-days post-infection with Mycobacterium, using previous hRSV infected mice, by flow cytometry and the expression of critical genes involved in the immune response by real-time quantitative reverse transcription polymerase chain reaction (RT-qPCR). Among the latter, we analyzed the expression of Heme Oxygenase (HO)-1 in an immunization scheme in mice. Our data suggest that a pre-infection with hRSV has a conditioning effect promoting lung pathology during a subsequent mycobacterial challenge, characterized by increased infiltration of innate immune cells, including interstitial and alveolar macrophages. Our data also suggest that hRSV impairs pulmonary immune responses, promoting secondary mycobacterial colonization and lung survival, which could be associated with an increase in the expression of HO-1. Additionally, BCG is a commonly used vaccine that can be used as a platform for the generation of new recombinant vaccines, such as a recombinant BCG strain expressing the nucleoprotein of hRSV (rBCG-N-hRSV). Therefore, we evaluated if the immunization with rBCG-N-hRSV could modulate the expression of HO-1. We found a differential expression pattern for HO-1, where a higher induction of HO-1 was detected on epithelial cells compared to dendritic cells during late infection times. This is the first study to demonstrate that infection with hRSV produces damage in the lung epithelium, promoting subsequent mycobacterial colonization, characterized by an increase in the neutrophils and alveolar macrophages recruitment. Moreover, we determined that immunization with rBCG-N-hRSV modulates differentially the expression of HO-1 on immune and epithelial cells, which could be involved in the repair of pulmonary tissue.